Rabbits - Patchett, Fiona (New York Usborne Publishing, 1999)
A practical guide for any young pet lover who wants to know how to look after a rabbit. There's lots of information on choosing a rabbit, the equipment you will need, what to feed it and how to clean out its hutch. There are also tips about grooming, playing with your rabbit and how to make friends with it.
5 - 9
Keywords: Pet rabbits; Rabbits